Novel L-shaped gurney flap for rotorcraft vibration reduction - Motta, V.; Quaranta, G. (My University, 2015)
This work concerns an assessment of the rotor blade vibration reduction capabilities of a novel L-shaped trailing edge Gurney Flap. The primary effect of this L-tab is represented by a modification of the reference airfoil mean line shape, both in terms of camber and chord length, this latter being related to the two counter rotating vortical structures developed past the tab vertical prong. Previously validated computational fluid dynamics results are exploited to develop a physically based thin-line reduced order model, which successfully reproduces the mean line modifications induced by the L-tab, in addition to accurately capture the steady aerodynamic forces and the first harmonic of the unsteady loads generated by fixed configurations of the airfoil L-tab system and by oscillating motions of the movable device. A thin-line linear model is also developed for a blade section equipped with a classical trailing edge flap. Comparisons of the aerodynamic loads generated by these two movable devices for equal input oscillation laws, allow to estimate the ranges of reduced frequency where the L-tab is expected to perform better with respect to the trailing edge flap and vice-versa. These two reduced order models are then exploited to build up two separate three degrees of freedom linear aerostructural models for a blade equipped with a partial span L-tab or a trailing edge flap. A higher harmonic control algorithm is then applied and compared between the two devices to reduce separately the N/rev harmonics of the blade root rotating frame vertical force, flapping and feathering moments. A significant reduction of the vibratory loads is obtained. Moreover, the attainment of similar results with a well known trailing edge device, such the classical flap taken under consideration, is a further confirmation of the potential feasibility of this novel L-tab as an effective alternative mean for vibration reduction on rotor blades.
Keywords: Dynamics